Absolute Oral Bioavailability of Creatine Monohydrate in Rats: Debunking a Myth - Eman A. Alraddadi; Ryan Lillico; Jonathan L. Vennerstrom; Ted M. Lakowski; Donald W. Miller (MDPI AG, 2018)
Creatine is an ergogenic compound used by athletes to enhance performance. Supplementation with creatine monohydrate (CM) has been suggested for musculoskeletal and neurological disorders. Until now, little is known about its pharmacokinetic profile. Our objective was to determine the oral bioavailability of CM and the influence of dose on oral absorption. Rats were dosed orally with low dose (10 mg/kg) or high dose (70 mg/kg) 13C-labeled CM. Blood samples were removed at various time points. Muscle and brain tissue were collected at the conclusion of the study. Plasma and tissue levels of 13C-labeled creatine were determined using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Physiologically based pharmacokinetic (PBPK) models of CM were built using GastroPlus™. These models were used to predict the plasma concentration-time profiles of creatine hydrochloride (CHCL), which has improved aqueous solubility compared to CM. Absolute oral bioavailability for low dose CM was 53% while high dose CM was only 16%. The simulated Cmax of 70 mg/kg CHCL was around 35 μg/mL compared to 14 μg/mL for CM with a predicted oral bioavailability of 66% with CHCL compared to 17% with CM. Our results suggest that the oral bioavailability of CM is less than complete and subject to dose and that further examination of improved dosage formulations of creatine is warranted.